2016
DOI: 10.1016/j.aller.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

IgE cross-reactivity of peanut with walnut and soybean in children with food allergy

Abstract: Although the clinical significance of the cross-reactivity of peanut specific IgE with walnut and soybean protein extracts has not been established, we believe that individuals who are allergic to peanuts need to be cautious about consuming walnuts and soybeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Despite this, the clinical significance of this fact is still uncertain. 41 The results of this study support a significant cross-reactivity between peanut and soybean.…”
Section: Discussionsupporting
confidence: 70%
“…Despite this, the clinical significance of this fact is still uncertain. 41 The results of this study support a significant cross-reactivity between peanut and soybean.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, in peanut-allergic patients, co-sensitization to lupine (82%), pea (55%), and soybean (87%) is often seen [ 21 ]. Peanut specific immunoglobulin E (IgE) was inhibited by soybean (26%) extract, thus indicating possible cross-reactivity [ 22 ]. Klemans et al concluded that Ara h 2 had the best predictive value for diagnosing peanut allergy in adults [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are at least 18 allergen components in peanut; Ara h 1, Ara h 2, and Ara h 3 are the major allergens and Ara h 8 is defined as the minor allergen, and these share a significant amino acid similarity with the allergens Gly m 4 and Bet v 1 [ 28 , 29 ]. Bet v 1 is the major allergen component of birch pollen, and a number of reports have been published on its cross-reactivity with peanut allergens [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%